PEMBAHARUAN PENDIDIKAN ISLAM TRADISIONAL MENGHADAPI ERA SOCIETY 5.0 - Ersi Ersi; Zainuddin Zainuddin (Raudhah - Proud To Be Professional, 2023)
This study aims to describe the renewal of Traditional Islamic education in facing the challenges of Era Society 5.0. The research method used is library research with documentation data collection techniques. While the analysis of the data used is content analysis (content analysis). The results of this study are that in facing Era Society 5.0, traditional Islamic education is required to be able to adapt to the changes and needs of the times by carrying out various updates, both in terms of curriculum and in terms of human resources so as to be able to deliver students to have the skills and knowledge needed. For this reason, students must be equipped with various kinds of knowledge and skills including; first, equip students to have critical thinking skills and problem solving. Second, equip students with communication skills. Third, developing the creativity and innovation of the students, and fourth, being able to collaborate